Excision repair cross-complementing group 1 (ERCC1) overexpression inhibits cell apoptosis and is associated with unfavorable prognosis of esophageal squamous cell carcinoma. Issue 31 (August 2018) - Peng, Haiying; Yao, Shaobo; Dong, Qingyu; Zhang, Yanxia; Gong, Weihong; Jia, Zhongyao; Yan, Li
Abstract : Abstract: Excision repair cross-complementing group 1 (ERCC1) functions as a nucleotide excision repair (NER) enzyme. Altered ERCC1 expression or function is closely associated with cancer development and progression. This study determined the association of ERCC1 expression with survivin expression, clinicopathological characteristics, and survival of esophageal squamous cell carcinoma (ESCC) patients after postoperative concurrent chemoradiotherapy. Tissue specimens from 102 resected ESCC patients were acquired for immunohistochemical analysis of ERCC1 and survivin protein expression. ERCC1 expression was detected in 62.7% of ESCC tissues and in 9.8% of normal squamous epithelium tissues ( P < .01), while survivin expression was detected in 60.8% of ESCC tissues and in 19.6% of normal squamous epithelia ( P < .01). ERCC1 overexpression associated with advanced tumor clinical stage and lymph node metastasis ( P < .05), but not with tumor size, depth of invasion, or differentiation ( P > .05). ERCC1 overexpression was also associated with survivin levels ( r = 0.42, P < .01) and worse progression-free survival of ESCC patients after concurrent chemoradiotherapy. Multivariate analysis data revealed that ERCC1 and survivin protein expression were independent predictors of overall survival of ESCC patients after chemotherapy and/or radiotherapy ( P < .05). ERCC1 overexpression is an important phenotype that is associated with ESCC lymph node metastasis and advanced tumor clinical stages. ERCC1 expression may also inhibit ESCC cell apoptosis via regulating survivin expression, and ERCC1 and survivin overexpression are independent predictors of prognosis for ESCC patients who receive chemotherapy and/or radiotherapy.